Teachers’ Perspectives on their roles in EFL Curriculum Development: Wollo and Samara Universities of Ethiopia in focus - Sualih Yimer, Abdusomed (Universitas Sulawesi Barat, 2025)
The aim of this study was to investigate teachers’ perspectives on their roles in English as Foreign Language (EFL) curriculum development in two Ethiopian universities, Wollo and Samara. The study was descriptive in design accompanied by mixed research approach. Participants of the study were EFL teachers of the two universities (n=32). The study employed parallel mixed sampling technique merging census and purposive sampling techniques concurrently. Data were gathered via questionnaires and interviews. The data were analyzed using convergent parallel data analysis method. Findings of the study revealed that majority of the teachers had active roles in curriculum implementation though they had very restricted involvement in curriculum designing. Some teachers had moderately limited involvement in curriculum evaluation and improvement. Majority of the teachers also had negative perspectives on their roles in curriculum development process. Behind teachers’ negative perspectives, problems like less inclusiveness of curriculum development, little worth for teachers’ voice in curriculum development, predominance of top-down curriculum development approach, inequitable opportunities for curriculum development programs as well as inadequate budget and time for curriculum development were identified. Teachers’ negative perspectives on their roles in curriculum development process in turn imparted undesirable impediments on teaching practices. Correspondingly, recommendations like necessities of teachers’ adequate involvement in curriculum development, equitable criteria for selecting participants in curriculum development, practical concerns for teachers’ credible ideas in curriculum development, replacing top-down curriculum development approach with its bottom-up counterpart and sustenance of teachers’ motivations to enhance EFL curriculum were forwarded.